The Effectiveness of Tai Chi Exercises on Postural Balance in the Elderly in RS. Hermina Depok - Maulina, Luluk; Hamzah, Arfian (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: As a person gets older, the functions of his/her body organs decrease. A person will experience many declining abilities, including a decrease in postural balance. Postural balance is the ability to maintain the body in an upright position by aligning the centre of gravity and base of support with appropriate body movements and using minimal muscle activity without excessive muscle contraction. Decreased balance function will increase the risk of falls in the elderly, therefore balance is the most important problem for every elderly. Currently, many methods or types of exercises aim to improve postural balance. One of them is the provision of gymnastics. Tai Chi exercise is an exercise originating from China, which consists of various sequences of movements with the aim of training body coordination and balance. To determine the effectiveness of Tai Chi exercises on postural balance in the elderly. Methods: This study used a quasi-experimental method with the research design used was pretest and posttest two group design. The sample in the study was elderly aged 60 years and over with a total of 32 person, where the sample was divided into 2 groups, namely 16 person in the control group and 16 person in the treatment group. The measuring instrument used was the Functional Reach Test which was carried out before and after being given Tai Chi exercises. The research was conducted at RS Hermina Depok, Physiotherapy Clinic, starting from January to March 2023. Results: This study shows that Tai Chi exercises significantly improve postural balance in the elderly (p=0.001). Conclusion: The provision of Tai Chi exercises is significant in improving postural balance in the elderly.